The Preservations of Failures in Business in Ambrose Bierce’s The Failure of Hope and Wandel - Syaif, Serly Maulina; Siadari, Yoshua Veron Handika Putra; Firzatullah, Muchammad Daffa; Pasopati, Rommel Utungga (Foremost Journal, 2024)
This research investigates to reveal the obstacles faced by the main characters Jabez Hope and Pike Wandel in Ambrose Bierce’s flash fiction entitled The Failure of Hope and Wandel. Hope and Wandel run an ice business together and face several knowledge problems. Using qualitative method and explorative approach, this article analyzes how the excess of obstacles encountered at the beginning of the business process negatively affects the formation of qualified enterprises. This research is reviewed through Patrick A. Gaughan's theory of causes of business failure including experience, fraud, and disaster. Both Hope and Wandel never know that ice is abundant but will easily melt when the spring comes. In conclusion, this story is imaginative but real in the sense that any business could easily collapse if the owner forgets to pay attention to the core of the business materials.